Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha (Studi Kasus Mahasiswa Program Studi Pendidikan Ekonomi STKIP Pembangunan Indonesia) - Oktarina, Harti; Agung, Eka Adnan; Aswad, Sitti Hajar (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
The aim of this research is to know: 1) The effect of Entrepreneurship Education on Entrepreneurial Interest in STKIP Pembangunan Indonesia economic education students, 2) the effect of Earning Expectations on Entrepreneurial Interest in STKIP Pembangunan Indonesia economic education students, 3) The effect of Family Environment on Entrepreneurship Interest in Economic Education students STKIP Pembangunan Indonesia, and 4) The Effect of Entrepreneurship Education, Earning Expectations, and Family Environment on Entrepreneurial Interest in STKIP Pembangunan Indonesia economic education students.This research was causal comparative research. The population in this research are students of economic education who had participated in entrepreneurship courses with a sample of 194 students. Methods of data collection in this research using questionnaire. The instrument test was do to 30 students of economic education STKIP Pembangunan Indonesia. Classic assumption test includes normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The hypothesis test used is multiple regression analysis.The simultaneous test results showed that Entrepreneurship Education, Earning Expectations and Family Environment had an effect on Entrepreneurial Interest in STKIP Pembangunan Indonesia economic education students with a significance value of 0.003 <alpha value of 0.05. Based on the results of the partial test show that: 1) Entrepreneurship Education influences the interest in entrepreneurship with a significance value of 0.047 <alpha value 0.05, 2) Income Expectations influence the interest in entrepreneurship with a significance value of 0.022 <0.05, and 3) Family Environment influences interest in entrepreneurship with a significance value of 0.004 <alpha value of 0.05.Â Keywords: Entrepreneurship Education, Earnings Expectations, Family Environment, Interest in Entrepreneurship